Upaya Mitigasi Meningkatkan Kapasitas Bangunan Terhadap Ancaman Bencana Tanah Longsor di Kalirejo, Kokap, Kulonprogo - Sely Novita Sari; Anggi Hermawan; Rizqi Prastowo (Universitas Islam Raden Rahmat, Malang, 2023)
Pre-Disaster Mitigation is carried out to reduce casualties and material casualties when a landslide occurs. Research on the analysis of the potential for landslides in the Kalirejo area using various methods has been carried out, so further research will be carried out on the analysis of building non-conformity measures based on the evaluation of typical simple walls. Evaluation actions are needed for strengthening, restoring or relocating buildings in landslide-prone areas, so that the government will provide recommendations for strengthening and building restoration activities in accordance with the evaluation form. The method used was to distribute closed and open questionnaires to analyze the actions to be taken if the existing buildings were not in accordance with the standards. The conclusion obtained is that 45% of the reinforcement activities can be carried out. There were 22 buildings that could not be strengthened so they were left as they were. For repaired activities, it was found that there were 5 building conditions that could not be returned or around 12.5% of the building conditions that were left as they were. For the condition of the building that can be repaired by 87.5% of the condition of the building.